2020
DOI: 10.1111/cpf.12635
|View full text |Cite
|
Sign up to set email alerts
|

Muscle swelling following blood flow‐restricted exercise does not differ between cuff widths in the proximal or distal portions of the upper leg

Abstract: The purpose was to understand how wider cuffs, covering larger portions of the limb, may affect acute muscle swelling when used during low‐load knee extension exercise with blood flow restriction. A total of 96 individuals (53 females and 43 males) completed two visits, with visit one used for measuring maximal strength and arterial occlusion pressure (AOP), and visit two to compare between a narrow (5 cm) and a wide (12 cm) cuff for acute changes in muscle thickness and echo intensity following exercise. Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…The current study’s results presented a temporary increase in mCSA at IMM-POST in males which may have been caused by the BFR quad sets, but this was a modest 4.0% and insufficient to be significantly greater than any other time point. These results contrast with previous studies that have identified significant changes in muscle size variables (MT and mCSA) of 10.7–12.6% from PRE to after exercise following knee extensions performed with BFR [ 10 12 ]. However, the exercises used included concentric, low-load (20–30%) voluntary contractions at varying inflation pressures (140 mmHg) or relative percentages [50% arterial occlusion pressure (AOC)].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The current study’s results presented a temporary increase in mCSA at IMM-POST in males which may have been caused by the BFR quad sets, but this was a modest 4.0% and insufficient to be significantly greater than any other time point. These results contrast with previous studies that have identified significant changes in muscle size variables (MT and mCSA) of 10.7–12.6% from PRE to after exercise following knee extensions performed with BFR [ 10 12 ]. However, the exercises used included concentric, low-load (20–30%) voluntary contractions at varying inflation pressures (140 mmHg) or relative percentages [50% arterial occlusion pressure (AOC)].…”
Section: Discussioncontrasting
confidence: 99%
“…These studies have presented mixed results, with Hackney et al [ 11 ] showing no significant differences compared to baseline in rectus femoris mCSA immediately after and 5-minutes after BFR knee extensions when compared to low-load non-BFR exercises. Conversely, the MT of the vastus lateralis can be elevated immediately after BFR knee extensions with a concomitant decrease in EI [ 10 ] and MT can be elevated up to 3-hours after BFR knee extensions compared to baseline [ 12 ], purportedly due to local swelling. Additionally, the perceived effort of BFR-mediated “work” has been reported to be much higher than non-BFR movements, hence why a standard protocol for BFR includes only 20–30% 1-repetition maximum load during dynamic, concentric resistance exercises [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When lifting loads at or above 60% 1RM, intramuscular pressure is high due to muscle tension, and thus blood flow during exercise is occluded (Sjøgaard et al, 1988;Golas et al, 2015). Also, blood flow during recovery in the latter four sets in all trials, may be compromised due to muscle swelling, as a result of osmotic changes and fluid shifts into the muscle (Sjøgaard et al, 1988;Ploutz-Snyder et al, 1995;Bell et al, 2020). Thus, if blood flow during exercise and recovery is reduced due to muscle tension and muscle swelling, Results are mean ± SD (90% confidence intervals).…”
Section: Discussionmentioning
confidence: 99%